-2x=-2x-2

Simple and best practice solution for -2x=-2x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x=-2x-2 equation:


Simplifying
-2x = -2x + -2

Reorder the terms:
-2x = -2 + -2x

Add '2x' to each side of the equation.
-2x + 2x = -2 + -2x + 2x

Combine like terms: -2x + 2x = 0
0 = -2 + -2x + 2x

Combine like terms: -2x + 2x = 0
0 = -2 + 0
0 = -2

Solving
0 = -2

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 20/1.6=x | | -2x-1=-5x+8 | | 12x+12=3(4x+6) | | 3/5x=4/5+12/5 | | 2(x+3)=3x | | 24x+12=2(12x+12) | | 15x-40y+35z= | | 2x-4=-4x+14 | | 1=2(1)-1 | | 3(x+2)=2c | | 3x+4=-3x+28 | | (2a^4b-3a^4+6b)+(5a^4-9a^4-8b)= | | -2x+1=2x-19 | | 8(x-7)=6(x-4) | | 3x^2-5+1=0 | | 2x+108=8x+60 | | 3x+12y=-30 | | -7x+5(8+9n)=4(9n+1) | | -(7x+3)-(5x-3)=7-(2x+1) | | 2Y=3X-Y | | 3(-2)-1=-2-5 | | 3x+41=65 | | 12(-2b-12)=-6(-3b+10) | | -2x+1=3x-9 | | -5x=-2x-6 | | 7500x=5900x+88000 | | (x+72)(x+48)=6912 | | -15-32n=4(-8n+4) | | 120-5a+7=8a-16a-35 | | 8y+1=9y-7 | | 4x+89=7x-74 | | 3x+2=3x-3 |

Equations solver categories